Difficulties in understanding mechanical waves: Remediated by problem-based instruction - Kanyesigye, Stella Teddy; Uwamahoro, Jean; Kemeza, Imelda (Physical Review Physics Education Research, 2022)
This study aimed at analyzing the impact of problem-based learning (PBL) in improving physics students’ conceptual understanding of mechanical waves. This study used a quasi-experimental, pretest–post-test control group design with PBL instruction as a teaching intervention. The participants of this study were 239 physics students from 19 secondary schools in Western Uganda. We analyzed data with SPSS v.23.0 using repeated two-way analysis of variance tests. We found that unlike the superposition of mechanical waves concepts, PBL effectively improves students’ understanding of propagation, reflection, and standing waves more than the usual or traditional teaching method. Teachers were recommended to teach with PBL to assess students’ difficulties to remedy them and uplift their understanding
Keywords: Problem-based learning; Conceptual understanding; Mechanical waves